2013
DOI: 10.1111/jpn.12104
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recombinant duck follistatin protein on embryonic muscle development and gene expressions

Abstract: Follistatin (FST) acts as a positive regulator of muscle development by inhibiting the activities and expression of myostatin. The recombinant duck FST protein was injected into hatching eggs and was also added to the medium of duck myoblast to study its role on duck embryonic muscle development and gene expressions. Duck embryo weight increased 3.49% (p > 0.05) in FST treatment group as compared with control group, but minor effects were found on leg or breast muscle weights of ducklings at 2 days post-hatchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies in our laboratory showed that recombinant duck FST protein could promote muscle hypertrophy in the post-hatching duck by inducing satellite cell proliferation [ 8 ]. However, FST played minor roles in embryonic skeletal muscle development [ 9 ]. To date, the regulatory mechanism of FST in the skeletal muscle development of birds remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in our laboratory showed that recombinant duck FST protein could promote muscle hypertrophy in the post-hatching duck by inducing satellite cell proliferation [ 8 ]. However, FST played minor roles in embryonic skeletal muscle development [ 9 ]. To date, the regulatory mechanism of FST in the skeletal muscle development of birds remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, Pax7 mRNA expression was upregulated in breast and leg muscle, MyoD mRNA was increased only in leg muscle while Myf5 mRNA was upregulated only in breast muscle. Moreover, the expression of myostatin was downregulated in both muscle types ( 206 ). The effects of vitamin C on duck embryos' hatchability were investigated by Nowaczewski et al ( 207 ).…”
Section: In Ovo Effects In Other Avian Speciesmentioning
confidence: 99%